A novel in vitro framework for understanding aroma interactions with the oronasal mucosa - Ford, Clive (2022)
An overview is presented of the olfactory mucosa, volumetric air flow through the geometry of the nasal and oral cavity and a review of the constituent parts of oro-nasal surfactants, saliva and nasal mucus. Discussed is the physical chemistry of dictating the behaviour of aroma in aqueous solutions. Previous investigations into the techniques deployed to describe aroma interactions with proteins, lipids, and biological system such as the oro-nasal mucosa.